Crisi economica, malattie croniche e diseguaglianze nella salute - Maciocco, Gavino (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The main aim of the paper is to start from the Zapf model concerning the objective and subjective dimensions of well-being in order to suggest an investigative strategy oriented toward studying urban quality of life by geo-referencing data. In particular, this approach has the main objective of explaining - thanks to the mapping of objective and subjective variables - well-being, deprivation, dissonance and adaptation attitudes of individuals. For this purpose a simulation model has been developed. The text also deals with methodological issues linked to the concrete application of the model itself.